Complex aortic plaques: hidden danger in aortic stenosis. Role of transesophageal echocardiography - Benites-Yshpilco, Lindsay (2024)
Aortic stenosis is associated with aortic plaques in up to 85% of cases because they share risk factors and pathogenic pathways. Intrinsically, complex aortic plaques carry a high risk of stroke, which has also been demonstrated in the context of aortic stenosis, especially in patients who underwent percutaneous or surgical replacement. Transesophageal echocardiography (TEE) is the imaging test of choice to detect plaques in the thoracic aorta and classify them as complex plaques. Furthermore, the 3D modality allows us to better specify its dimensions and anatomical characteristics, such as added thrombi or the presence of ulcers inside. This review aims to evaluate the use of TEE to detect complex aortic plaques in patients with an indication for percutaneous or surgical aortic valve replacement. To highlight the association between aortic stenosis and complex aortic plaques, we attached to the review some TEE studies from our experience.